A TV-Gaussian prior for infinite-dimensional Bayesian inverse problems and its numerical implementations. (27th May 2016) - Yao, Zhewei; Hu, Zixi; Li, Jinglai
Abstract: Many scientific and engineering problems require to perform Bayesian inferences in function spaces, where the unknowns are of infinite dimension. In such problems, choosing an appropriate prior distribution is an important task. In particular, when the function to infer is subject to sharp jumps, the commonly used Gaussian measures become unsuitable. On the other hand, the so-called total variation (TV) prior can only be defined in a finite-dimensional setting, and does not lead to a well-defined posterior measure in function spaces. In this work we present a TV-Gaussian (TG) prior to address such problems, where the TV term is used to detect sharp jumps of the function, and the Gaussian distribution is used as a reference measure so that it results in a well-defined posterior measure in the function space. We also present an efficient Markov Chain Monte Carlo (MCMC) algorithm to draw samples from the posterior distribution of the TG prior. With numerical examples we demonstrate the performance of the TG prior and the efficiency of the proposed MCMC algorithm.